Two Arabidopsis cyclin promoters mediate distinctive transcriptional oscillation in synchronized tobacco BY-2 cells. - Shaul, O (1996)
Cyclins are cell cycle regulators whose proteins oscillate dramatically during the cell cycle. Cyclin steady-state mRNA levels also fluctuate, and there are indications that both their rate of transcription and mRNA stability are under cell cycle control. Here, we demonstrate the transcriptional regulation of higher eukaryote cyclins throughout the whole cell cycle with a high temporal resolution. The promoters of two Arabidopsis cyclins, cyc3aAt and cyc1At, mediated transcriptional oscillation of the beta-glucuronidase (gus) reporter gene in stably transformed tobacco BY-2 cell lines. The rate of transcription driven by the cyc3aAt promoter was very low during G1, slowly increased during the S phase, peaked at the G2 phase and G2-to-M transition, and was down-regulated before early metaphase. In contrast, the rate of the cyc1At-related transcription increased upon exit of the S phase, peaked at the G2-to-M transition and during mitosis, and decreased upon exit from the M phase. This study indicates that transcription mechanisms that seem to be conserved among species play a significant role in regulating the mRNA abundance of the plant cyclins. Furthermore, the transcription patterns of cyc3aAt and cyc1At were coherent with their slightly higher sequence similarity to the A and B groups of animal cyclins, respectively, suggesting that they may fulfill comparable roles during the cell cycle.